Natural Regrowth of Mangrove Five Years After a Large-Scale Disturbance - Bryan Joseph Matillano; Mark Kevin Aleluya; Sherwin Ray Andoque; John Ricafort Fabicon; Getty Keith Ripalda (BIODIVERS - BIOTROP Science Magazine, 2023)
Haiyan, the strongest typhoon on landfall damaged mangrove covers resulting to uprooting, cutting off trunks, total defoliation and eventually death. After five years, Cancabato Bay were monitored for mangal succession and natural regrowth. Basal area was computed using diameter by breast height to estimate recovery. New species reappeared compared to the baseline study of GIZ (2014). Mangroves manifested regrowth and should be given time for natural regeneration and colonization. Natural succession patterns should be considered in human-assisted rehabilitation after disturbance.